Professional iPhone and iPod touch programming building applications for Mobile Safari - Wagner, Richard (Wiley Pub., 2008)
Provides information on designing and implementing mobile applications for the iPhone and the iPod touch.
Print version record
Keywords: Cell phones -- Technological innovations; Internet telephony; iPhone (Smartphone) -- Programming; iPod (Digital music player) -- Programming; Téléphonie Internet; iPhone (Téléphone intelligent); Programmation; iPod (Lecteurs de musique numérique); Programmation; Téléphones cellulaires; Innovations; COMPUTERS; Web; Web Programming; Internet software; iPhone (Smartphone); iPod (Digital music player)